Table of contents
- 0. Functions7h 52m
- Introduction to Functions16m
- Piecewise Functions10m
- Properties of Functions9m
- Common Functions1h 8m
- Transformations5m
- Combining Functions27m
- Exponent rules32m
- Exponential Functions28m
- Logarithmic Functions24m
- Properties of Logarithms34m
- Exponential & Logarithmic Equations35m
- Introduction to Trigonometric Functions38m
- Graphs of Trigonometric Functions44m
- Trigonometric Identities47m
- Inverse Trigonometric Functions48m
- 1. Limits and Continuity2h 2m
- 2. Intro to Derivatives1h 33m
- 3. Techniques of Differentiation3h 18m
- 4. Applications of Derivatives2h 38m
- 5. Graphical Applications of Derivatives6h 2m
- 6. Derivatives of Inverse, Exponential, & Logarithmic Functions2h 37m
- 7. Antiderivatives & Indefinite Integrals1h 26m
3. Techniques of Differentiation
Product and Quotient Rules
Problem 92a
Textbook Question
Suppose the line tangent to the graph of f at x=2 is y=4x+1 and suppose y=3x−2 is the line tangent to the graph of g at x=2. Find an equation of the line tangent to the following curves at x=2.
y = f(x)g(x)
![](/channels/images/assetPage/verifiedSolution.png)
1
Step 1: Identify the given information. We have two functions, f(x) and g(x), with their respective tangent lines at x=2. The tangent line to f(x) at x=2 is y=4x+1, which implies that f'(2)=4 and f(2) is the y-value when x=2, which can be found by substituting x=2 into the equation of the tangent line. Similarly, the tangent line to g(x) at x=2 is y=3x−2, which implies that g'(2)=3 and g(2) is the y-value when x=2, found by substituting x=2 into the equation of the tangent line.
Step 2: Use the product rule to find the derivative of y=f(x)g(x). The product rule states that if y=u(x)v(x), then y'=u'(x)v(x) + u(x)v'(x). Here, u(x)=f(x) and v(x)=g(x), so y'=f'(x)g(x) + f(x)g'(x).
Step 3: Substitute x=2 into the derivative found in Step 2. This gives y'(2)=f'(2)g(2) + f(2)g'(2).
Step 4: Substitute the known values from Step 1 into the expression from Step 3. We have f'(2)=4, g'(2)=3, and the values of f(2) and g(2) can be found from the tangent line equations.
Step 5: Use the result from Step 4 to write the equation of the tangent line to y=f(x)g(x) at x=2. The equation of a tangent line is y-y_1=m(x-x_1), where m is the slope found in Step 4, and (x_1, y_1) is the point on the curve at x=2, which can be found by evaluating y=f(x)g(x) at x=2.
Recommended similar problem, with video answer:
![](/channels/images/assetPage/verifiedSolution.png)
This video solution was recommended by our tutors as helpful for the problem above
Video duration:
6mPlay a video:
Was this helpful?
Related Videos
Related Practice